Optimization of IC 32-pin QFP Pick Up Parameters - Wikanta, Prasaja; Sitompul, Adravia Lisbeth Claudia; Wivanius, Nadhrah; Arifin, Muhammad; Nakul, Fitriyanti (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to optimize the picking parameters of 32-pin Quad Flat Package (QFP) IC components on the SM421 pick-and-place machine operating at the Teaching Factory for Electronics Manufac-turing (TFME) of Batam State Polytechnic. Currently, the machine has not been optimized, so users must manually adjust the compo-nent dimensions and parameter settings before operation. This re-sults in significant setup time and reduces process efficiency. The method used in this study is Design of Experiments (DOE) to sys-tematically evaluate various parameter settings. The experimental results show that certain configurations can reduce setup time and improve component placement accuracy. These findings contribute significantly to improving machine performance and operational ef-ficiency in the Surface Mount Technology (SMT) assembly process. In conclusion, optimizing the 32-pin IC picking parameters on the SM421 machine can improve the productivity and effectiveness of the assembly process.